The application of islamic arts decoration in mosque interior : a case study of the traditional mosque in Melaka / Norzalifa Zainal Abidin - Zainal Abidin, Norzalifa (Institute of Graduate Studies, UiTM, 2012)
This research discussed the concept of ‘Tawhid’ as the doctrine in Islam; and the way Islam perceives Beauty in its decorative arts as a mean of contemplation and Remembering Allah. In order to understand these hidden functions and messages, the overall approach, roles, functions and typologies of decoration are explained. The uniqueness of Islamic Arts’ characteristics, roles, meanings and principles are governed universally by the Islamic doctrine – ‘Tawhid’ which expressed Oneness and Unity towards Contemplation to the One God – Allah. By looking at these aspects, one can truly assess whether the current usage of decorative motifs in mosque is in full success or not. A cross-reference of these usages is established with the true roles and functions of these decoration motifs as decoration in relation to Islamic Art as a whole. Successful applications of the interior decorative motifs can then be established and recommended for future applications. It is the intention of the study to be as an impetus for other broader and more critical analyses which can be made by others to fully comprehend the underlying concepts of the decorative motifs in the mosque interiors.